Prethermalization in the cooling dynamics of an impurity in a Bose-Einstein condensate - Lausch, Tobias; Widera, Artur; Fleischhauer, Michael (Physical Review A, 2018)
We discuss the cooling dynamics of heavy impurity atoms in a Bose-Einstein condensate (BEC) by emission of Cherenkov phonons from scattering with the condensate. In a weakly interacting low-temperature condensate, different scattering processes result in a separation of time scales of the thermalization dynamics. Prethermalized states are formed with distinct regions of impurity momenta determined by the mass ratio of impurity and BEC atoms. This can be employed to detect the mass renormalization of the impurity upon the formation of a polaron and paves the way to preparing nonequilibrium impurity-momentum distributions.
CRIS-Team Scopus Importer:2023-03-27